Thermal conductivity of IODP Hole 389-M0100A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Thermal conductivity data from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). Measurements of thermal conductivity took place during the onshore phase of the expedition, which took place between 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Thermal conductivity was measured with the TeKa TK04 system using the HLQ probe H11047. For each measurement five measuring cycles are generally recorded with a 10 minutes pause between measurements. Archive split cores were measured at room temperature. From these recordings the coefficient pf thermal conductivity was then calculated according to the formula given in Webster et al. (2025). Thermal conductivity measurements were generally taken every 10 meters at locations with even split core surfaces to increase rock contact with the probe. However, the uneven surfaces of the dominating lithologies (reef limestones and vesicular lava) prevented successful measurements in some sections. For further methodological information as well as a list of sections on which thermal conductivity measurements were successful see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025